Effectiveness of the periodontal treatment in the metabolic control of patients with diabetes mellitus - Maritza Peña Sisto; Milagros Calzado de Silva; Wendy Suárez Avalo; Liliana Peña Sisto; Eugenia González Heredia (Centro Provincial de Información de Ciencias Médicas, 2018)
A study of therapeutic intervention in 60 patients with diabetes mellitus and light periodontitis, assisted in the estomatological service of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba, aimed at determining if the treatment would favor the metabolic control of the affected patients, was carried out from November, 2015 to the same month in 2016. Two groups were formed at random  with 30 members each: a study group (even numbers) who received the initial phase of the treatment, radicular scrapring and smoothing; a control group (odd numbers), they were indicated initial phase and subgingival irrigations with chlorhexidine. Before and after the periodontal treatment  glycemia and glycosylated hemoglobin exams were carried out. The chi-square test of homogeneity was used for the comparison among these groups, with a significance of 95%. It was concluded that the periodontal therapy was effective in the metabolic control of the patients.